2002
DOI: 10.1159/000065868
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Infection of Lacertids with Lizard Erythrocytic Viruses

Abstract: Objective: Lizard erythrocytic viruses (LEVs) produce inclusions in the cytoplasm of erythrocytes, but their impact on the infected host is poorly understood. This work reports on an experimental study of the infection process in Lacerta monticola and Lacerta schreiberi from Serra da Estrela Mountain, Portugal. Methods: A time sequence light microscope and transmission electron microscope (TEM) study of the infection process was performed in peripheral blood erythrocytes of experimentally infected lizards. Vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
16
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 34 publications
3
16
1
Order By: Relevance
“…18,26 In some cases, erythrocytic inclusions have been associated with marked anemia, 17,26 but experimental infection has failed to reproduce anemia unless the lizards were maintained in a cold environment. 3 Many viral diseases of poikilothermic vertebrates are highly temperature dependent, including iridoviruses, and the current data does not differentiate among the relative roles of host and virus on temperature-dependence of disease. 19,30 Therefore, the pathogenicity of EIVs in reptiles is not well defined.…”
Section: Introductionmentioning
confidence: 83%
“…18,26 In some cases, erythrocytic inclusions have been associated with marked anemia, 17,26 but experimental infection has failed to reproduce anemia unless the lizards were maintained in a cold environment. 3 Many viral diseases of poikilothermic vertebrates are highly temperature dependent, including iridoviruses, and the current data does not differentiate among the relative roles of host and virus on temperature-dependence of disease. 19,30 Therefore, the pathogenicity of EIVs in reptiles is not well defined.…”
Section: Introductionmentioning
confidence: 83%
“…Pathology associated with erythrocytic necrosis virus infections in reptiles is unclear, but morphological changes in infected erythrocytes have been documented. A transmission study conducted with the lizards Lacerta monticola and Lacerta schreiberi showed that infection with these agents can, in some cases, become systemic and may lead to death [37]. Recently, a PCR was successfully used to detect an iridovirus in a ribbon snake with erythrocytic inclusions in Florida, USA.…”
Section: Iridoviridaementioning
confidence: 99%
“…52 Marschang et al isolated irido-like viruses of two different genera, Iridovirus and Ranavirus, from a four-horned chameleon, a green iguana, and a leaf-tailed gecko (Uroplatus fi mbriatus). 55 However, in some instances the virus infected leukocytes and killed the infected animals. 53 Lizard erythrocytic viruses (LEVs) have been described under the family Iridoviridae 54 and their pathogenicity (e.g., LEVs) is poorly understood.…”
Section: Iridovirusesmentioning
confidence: 99%
“…53 The genus Iridovirus had been described in insects but not reptiles, which suggests the possibility of transmission of iridoviruses from insects to reptiles. 55 Other reports of LEVs include nine fl ap-necked chameleons (Chamaeleo dilepis), 54 one Fischer's chameleon (Bradypodion fi scheri), 54 two four-horned chameleons, 56 and a high-casqued chameleon (Chamaeleo hoehnelli). Alves de Matos et al performed an experimental infection of two lizard species (Lacerta monticola and Lacerta schreiberi) and demonstrated that the infection was mostly restricted to erythrocytes.…”
Section: Iridovirusesmentioning
confidence: 99%